Il Carroccio di Cortenuova: Nord e Sud Italia tra Papato e Impero nella Cronaca di Salimbene de Adam - Nardone, Marina (Incontri. Rivista europea di studi italiani, 2013)
The Caroccio of Cortenuova Northern and Southern Italy between Papacy and Empire in the Cronaca of Salimbene de Adam Starting from a quote in recent literature on the Italian unification, this article attempts to explain the role played by the Italian Middle Ages in the construction of national memory and in the archeology of a prejudice. It admonishes that only a full recognition of the deep alterity of the Middle Ages can prevent misuses of medieval references. Next, it proceeds to discuss the quote in question, namely a reference to Salimbene de Adam’s well-known chronicle, and it examines what drove this Franciscan chronicler to change the final episode of the Battle of Cortenuova (1237). In his Cronaca Salimbene relates that, after Frederick II had beaten the Lombard League’s army and seized possession of the Carroccio, the symbol of communal autonomy and liberty, he offered it to the city of Rome, which, in turn, burned it. However, a still existing inscription testifies that the Carroccio was not an unwelcome gift for Rome at all. Despite this historical reality, the Franciscan chronicler preferred, as Ludovico Gatto has suggested, to present posterity with the image of a defiant Rome towards Frederick II, who was identified after all, in the Joachimite literature, as the Antichrist, the enemy of Christianity.